Effects of dietary protein levels on production performance, meat quality and flavor of fattening pigs - Wang, Dong; Chen, Guoshun; Chai, Minjie; Shi, Chengrui; Geng, Yiwen; Che, Yuyan; Li, Yancui; Liu, Shuaishuai; Gao, Yancheng; Hou, Haoxia (Frontiers in Nutrition, 2022)
This study aimed to evaluate the effects of dietary protein level on the production performance, slaughter performance, meat quality, and flavor of finishing pigs. Twenty-seven Duroc♂×Bamei♀ binary cross-bred pigs(60.86 ± 2.52 kg body weight) were randomly assigned to three groups, each group has three replicates, and each replicate has three pigs. Three groups of finishing pigs were fed 16.0%, 14.0%, and 12.0% crude protein levels diets, and these low-protein diets were supplemented with four limiting amino acids (lysine, methionine, threonine and tryptophan). The results showed that the pigs fed low-protein diets increased (P< 0.05) loin eye muscle area, and reduced (P< 0.05) heart weight, lung weight. The feed-weight ratio of the 14.0% protein group was reduced (P> 0.05); Dietary protein levels significantly affected the luminance (L24h), yellowness (b45min and b24h) (P < 0.05), reduced shear stress, muscle water loss, drip loss, the levels of crude fat (P< 0.05), and increased marbling score (P < 0.05)in the muscle of finishing pigs; The low-protein diets improved PUFA/TFA, PUFA/SFA (P > 0.05), and increased hexanal, E-2-heptenal, 1-octen-3-ol, EAA/TAA in the muscle of finishing pigs (P < 0.05); The results indicated that reduced the crude protein levels of dietary by 2.0% 4.0%, and supplementation with four balanced limiting amino acids had no significant effects on the production performance and slaughter performance of finishing pigs, and could effectively improve meat quality and flavor.